Reason maintenance in product modeling via open source CAD system - Zakaria Ibrahim
The present and future challenges of a new product design, forecasting and risk management launch strategy for a new product modeling decision process. This research project intends to propose and to look towards the development of a low-cost integrated CAD-CAPP-CAD/CAM product modeling system for the design and manufacture of a proposed product. It is a mapping between several design phases like functional design, technical design and physical design. The modeling data generation process begins with the drafting of a product to be maintained using the drafting of an open source CAD software system package. Open Source CAD system can prevent any time gap between failure (MTBF) of the original CAD software and Open Sources (OSCAD) CAD System. This product modeling alternative as an option to the existing original product modeling packages. The only limitation are limited functionality, communication domain and generation of the machine code. Open Source CAD system enable to resume the cost or budget constraint, built up the potential skills of the users and short courses are available on the network (Internet). This framework represents the prototype of a possible future Open Source CAD system. It works with basic design data, Integrated Development Environment (IDE) and in the future it can automatically generate a machining code to be executed on a machine tool. The framework shall be a modular system and reconfigurable in which consists of four main modules: (1) Components-Product Functions, (2) Model Synthesis, (3) Rough Layout Product Model and (4) Functional Behavior. The system is structured, making it easy to manage and extend. It unifies the functionalities of design modeling and real simulation under the same interface. Thanks to the use of IDE technology in the form of the embedded open source AD software, the machining simulation is also near real-time. The framework has been tested through various trial-and-error application, using a PC based technology. It has been proved that use of IDE technology allows the development of an open source CAD system. In addition, the research outcome can also support remote management and configuration, a feature that could be useful in an environment featuring multiple design modeling for example, design for manufacturing (DFM) system). It is a very rare research in this domain especially in Asia and Malaysia particularly. Open source CAD system is the system function which is not only a parametric 3D modeler but also. to allow the designer to easily modify the design by going back into the model history and changing its parameters. OPENCASCADE is one of the options open source CAD system software. Users will run a project to build, debug, have built, or for connecting those to the CNC machine tool by model it in open source CAD system software. Reason Maintenance in Product Modeling via Open Source CAD System research work in unique in south east Asia region and the pride will belong to the nation.